Effect of Mixing ACIDAL® with Drinking Water for Laying Hens on Production Performance - Bouassi , T.; Ameyapoh, Y.; Hamme, V. Van; Anani, K.; Adjrah, Y.; Decuypere, E.; Gbeassor, M.; Tona, K. (International Journal of Poultry Science, 2016)
Background: The ban of antibiotics use as growth factors since 2006 affects animal performance and economical viability of farms. Several alternatives including incorporation of organic acids in feed or drinking water in order to improve productivity were studied. Objective: The objective of this study is to mix ACIDAL with drinking water of hens in order to improve productivity. Methodology: The experiment was carried out with 360 ISA Brown hens (22-44 weeks of age), allocated to 3 groups (control, Aci 1 and Aci 2) of 120 birds each. The three groups received, respectively in drinking water 0, 1 and 2 mL of ACIDAL L–1. Prior to start, every 4 weeks and at the end of the treatments, samples of chicken droppings according to each group were collected and used to determine total Streptococcus and Escherichia coli and to check the presence of Salmonella. During treatments, amount of water consumption, feed intake, body weight, egg weight and egg component weights were recorded weekly. Results: Eggs produced were collected daily and every 2 weeks, the litter quality was assessed. Mixing of ACIDAL with drinking water of laying hens reduced significantly the number of total bacteria, eliminated completely Salmonella in the droppings, decreased feed intake and improved egg weights and body weight compared to control group witch litter was significantly wetter and more tendentiously crusty compared to those of treated groups. Conclusion: In opposite, there is no effect on water consumption, mortality rate, egg laying rate and ratios of albumen, yolk and shell.